Teaching traditions in physical education in France, Switzerland and Sweden: A special focus on official curricula for gymnastics and fitness training - Forest, Emmanuelle; Lenzen, Benoît; Öhman, Marie (European Educational Research Journal, 2018)
The aim of this paper is to identify and discuss similarities and differences between the curricula for physical education (PE) in secondary schools in Sweden, France and the canton of Geneva (Switzerland) in the light of PE teaching traditions (PETTs). Teaching traditions concern ideas about the goals of school disciplines and therefore about the kind of learning pupils are expected to acquire. The paper focuses more specifically on two subjects, gymnastics and fitness training, because these physical activities are liable to highlight the similarities and differences across contexts in terms of didactic transposition. A content analysis of current curriculum materials of the three countries was conducted taking the following dimensions into account: (a) the general structure of the curriculum texts; (b) the general recommendations; and (c) the learning outcomes expected from the pupils in terms of knowledge and values, with examples of contents in gymnastics and fitness training. The results show the entanglement of various PETTs in each country: PETT as Sport-Techniques primarily shapes French and Swiss-Genevan curricula, PETT as Health Education is more present in Sweden and, to a lesser extent, in Switzerland, while PETT as Physical Culture Education tends to be more visible in France.